(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main issue raised in this study is the values of character education of children in the Qur’an (Comparative Study of the Story of the Prophet Nuh as. with the story of Prophet Ibrahim as.). Furthermore, this subject matter is translated into three sub-problems, namely: (1) how is the description of the value of children’s character education in the Qur’an which was instilled by the Prophet Nuh as. and Prophet Ibrahim as.; (2) how is the comparison of the value of children’s character education in the Qur’an which was instilled by the Prophet Nuh a.s. and Prophet Ibrahim as.; (3) how the impact of the values of children’s character education instilled by the Prophet Nuh as. and Prophet Ibrahim.. This research is completely classified as library research and uses a pedagogical approach. Sources of data were obtained from documents in the form of verses of the Qur’an and the hadiths of the Prophet, interpretations, thematic interpretations, stories of the prophets, syarah hadith, and Islamic education books, children’s character education books relevant to this research. The data that has been collected were analyzed using descriptive analysis techniques. The results showed that the Prophet Nuh as. and Prophet Ibrahim. In instilling the value of character education in their children, there are values of character education for children in the Qur’an. The values of character education in children were instilled by the Prophet Nuh AS. namely: (1) monotheism; (2) worship; (3) morals which include: sincerity, environmental preservation on earth, independence, compassion and care, prayer, patience, gratitude, responsibility and warning (tanzīr), respect for achievement, hard work, obedient and obedient. While the values of character education for children instilled by Prophet Ibrahim a.s. namely: (1) monotheism; (2) worship; (3) morals which include: obedient and obedient, prayer, delivery of good news (tabsyir); Optimalization has offspring, social care, patient, polite and good speaker, appreciation and achievement, safe and away from polytheism, social care, patient, polite and good speaker, appreciation and achievement, safe and away from polytheism, care and tawakkal, settlement of descendants (al-Isakān al-Żurriyah) and responsibility, gratitude, istiqamah in establishing prayer, social care, anticipation of the future, keeping promises, honest (al-Ṣiddīq); benevolent, brave, generous. This research is expected to be useful as a contribution of thought and reference in the field of children’s character education in the Qur’an, especially in imitating the Prophet Nuh as. and Prophet Ibrahim. in instilling character values in everyday life.